Analysis of the current investment climate in Ukraine - Trygub, Inna; Genyk, Svitlana (My University, 2014)
Internal resources of Ukraine finan cethenational economy in the proper amount is not enough. Today Ukraine has established the legal framework for investment activities. So, Ukraine needs new mechanisms for attracting foreign direct investment and a significant improvement of the investment climate.
Keywords: еconomy; investment activities; improvement; business; Ukraine; економіка; інвестиційні дії; удосконалення; бізнес; Україна; кафедра ділової іноземної мови та міжнародної комунікації